Discovery of N-arylpyrroles as agonists of GPR120 for the treatment of type II diabetes. Issue 5 (1st March 2018) - Winters, Michael P.; Sui, Zhihua; Wall, Mark; Wang, Yuanping; Gunnet, Joseph; Leonard, James; Hua, Hong; Yan, Wen; Suckow, Arthur; Bell, Austin; Clapper, Wilmelenne; Jenkinson, Celia; et al.
Graphical abstract: The discovery of a novel series of N -arylpyrroles as agonists of GPR120 (FFAR4) is discussed. Compound27 is a potent GPR120 agonist, has good selectivity for related receptor GPR40 (FFAR1), has acceptable PK properties, and is active in 2 models of Type 2 Diabetes in mice. Abstract: The discovery of a novel series of N -arylpyrroles as agonists of GPR120 (FFAR4) is discussed. One lead compound is a potent GPR120 agonist, has good selectivity for related receptor GPR40 (FFAR1), has acceptable PK properties, and is active in 2 models of Type 2 Diabetes in mice.